Comparison and modeling of leachate transportation dominated by the field permeability with an anisotropic characteristic based on a large-scale field trial study. (March 2020) - Yin, Ke; Chan, Wei-Ping; Dou, Xiaomin; Lisak, Grzegorz; Wei-Chung Chang, Victor
Abstract: Permeability significantly affects leachate transportation. Yet, there often exists a gap for its measurements between laboratory and the field. To predict the fate and transport of heavy metals from IBA leaching, a large-scale field trial study was performed using a big column ( d  ×  h  = 3 m × 5.5 m) packed with 1-m thickness of IBA (approx. 10.6 tons) overlaid by 4-m sand layer. The determined field permeability ( k F ) was compared with that achieved from the laboratory, demonstrating a large disparity as much as 4 orders of magnitude likely due to IBA self-compaction. Indeed, back calculation using Blake-Kozeny 's equation unveiled that, the "effective" diameters were significantly reduced by 21–46%. k F also demonstrated an anisotropic characteristic associated with fingered flows, trapped bubbles and heterogeneous consolidation/cementation efficiencies. To quantify the effects by k F, we ran a mechanistic model to simulate the transport of 11 heavy metals under advection ( d h / d x  = 0.05 m/m), indicating dramatically prolonged breakthrough time from days to centuries. Interestingly, breakthrough time was comparable among various metal ions (0–16.6% of RSD), suggesting their synchronous movements. Metal flux under k F was predicted in the end to address its toxicity potential, demonstrating limited environmental impacts in presence of the USEPA criterion. Graphical abstract: Image 1 Highlights: Great discrepancy identified on permeability determined between the laboratory and the field. The effective permeability were anisotropic associated with heterogeneous boundaries. Heavy metal transport demonstrated strong impacts from the variation of permeability. Breakthrough of heavy metals had synchronous behaviors independent of species. Single metal impacts on the environment would be limited.